Hepatoprotective Effect of Merlot Grape Pomace Extract Against Acetaminophen Induced Damage in Mouse (Global Journal of Human-Social Science, 2024)
This study investigated the benefits of Merlot grape pomace extract EBUM in experimental acetaminophen-induced intoxication Swiss mice received the respective treatments for 7 days Control saline Silymarin 100 mg Kg EBUM 100 mg Kg and 500 mg Kg On the seventh day the acetaminophen control Silymarin and EBUM received a single dose of acetaminophen 500 mg kg After 24 hours the mice were sacrificed the blood and liver were collected for analysis of serum transaminases ALT and AST bilirubin hepatic markers of oxidative stress and histopathological analysis EBUM was able to prevent acetaminophen-induced hepatic necrosis with a significant reduction p 0 0001 in ALT and AST bilirubin as well as a significant increase in hepatic GSH and CAT levels The histological data are consistent with the transaminase results showing less liver damage in the treated groups when compared to the acetaminophen group The results allow us to infer that EBUM has a hepatoprotective effect against intoxication caused by acetaminophen in animal model proving to be a therapeutic alternative in preventing drug-induced liver damage